Sectoral price divergence between Korea and Japan - Seongman Moon (East Asian economic review, 2016)
This paper examines the persistent properties of 12 sectoral relative prices between Korea and Japan obtained following the Classification of Individual Consumption according to Purpose (COICOP) over the period of 1985-2016. Applying a new econometric method developed by Pesaran which controls for the cross-section dependence in a panel, we are not able to reject the hypothesis that the sectoral real exchange rates contain a common stochastic trend. On the other hand, the well-known panel unit root tests such as the IPS and LLC tests widely used by previous studies strongly reject the unit root hypothesis. Since the error term of the regression for our panel exhibits significant cross-section dependence, these opposite results justify that the use of the new econometric method is appropriate.
10.11644/KIEP.EAER.2016.20.4.319; 10.11644/KIEP.EAER.2016.20.4.319; 2862898-6; 2508-1667; East Asian economic review; 863610854